Space microsystems and micro/nano satellites - You, Zheng (Oxford Butterworth Heinemann, 2017)
Space Microsystems and Micro/Nano Satellites covers the various reasoning and diverse applications of small satellites in both technical and regulatory aspects, also exploring the technical and operational innovations that are being introduced in the field. The Space Microsystem developed by the author is systematically introduced in this book, providing information on such topics as MEMS micro-magnetometers, MIMUs (Micro-inertia-measurement unit), micro-sun sensors, micro-star sensors, micro-propellers, micro-relays, etc. The book also examines the new technical standards, removal techniques or other methods that might help to address current problems, regulatory issues and procedures to ameliorate problems associated with small satellites, especially mounting levels of orbital debris and noncompliance with radio frequency and national licensing requirements, liabilities and export controls, Summarizing the scientific research experiences of the author and his team, this book holds a high scientific reference value as it gives readers comprehensive and thorough introductions to the micro/nano satellite and space applications of MEMS technology.--Provided by publisher.
Electronic reproduction.
Keywords: Microspacecraft; Electronic books